PRESCRIBING PATTERN OF NUTRACEUTICALS IN ONCOLOGY: AN OBSERVATIONAL STUDY - KHAJURIA, KANIKA; GUPTA, SEEMA; SHARMA, RAHUL; KHAJURIA, VIJAY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Introduction: Nutraceuticals are products found in foods and fruits that are also used as medicines other than being used for nutrition. They provide physiological benefits and protection against chronic diseases. They include minerals, vitamins, amino acids, essential fatty acids, and medicinal herbs or other dietary substances used as supplements, for example, polyphenols, quercetin, co-enzyme Q, and genistein are in use due to their chemopreventive potential. Aim of Study: The aim of this study was to examine the prescribing pattern of nutraceuticals in cancer patients. Methods: The present cross-sectional and observational study was conducted in the outpatient department (OPD) of Oncology of GMC Jammu after getting approval from the Institutional Ethics Committee. Patients of either gender and diagnosed with carcinoma attending oncology OPD were included in the study. Fifty prescription slips were evaluated for the prescribing pattern of nutraceuticals. The data were analyzed in percentages. Results: Most of the patients were prescribed more than one nutraceutical. Most commonly prescribed nutraceuticals were vitamins (44%) which included vitamin A, B complex, C, and D followed by minerals (36%), essential amino acids (12%), beta-carotene (8%), coenzyme Q (6%), lycopene (6%), curcumin (4%), and wheatgrass (2%). Conclusion: Nutraceuticals are being increasingly prescribed to cancer patients. In our study, vitamins were the most commonly prescribed nutraceuticals. Most of them have antioxidant potential. Nutraceutical use may increase in the future due to their safety and therapeutic effects.